La Colonia Número 2, Pinotepa Nacional, Oaxaca 1933-1934 (Tzintzun, Revista de Estudios Históricos, 2019)
This article analyzes the formation and disappearance of the only colony that was established in Mexico with people of Mexican origin from the United States, thanks to the intervention of federal officials and businessmen during the first three decades of the 20th century. It is prominent because it is an example of the inability and disinterest of the actors involved to consolidate a settlement of this type, and the limited colonization policy that generally existed in Mexico.